2015
DOI: 10.1080/14786451.2015.1053392
|View full text |Cite
|
Sign up to set email alerts
|

Implications for current regulatory waste toxicity characterisation methods from analysing metal and metalloid leaching from photovoltaic modules

Abstract: The appropriateness of regulatory methods to characterise the toxicity of photovoltaic (PV) modules was investigated to quantify potential environmental impacts for modules disposed of in landfills. Because solar energy is perceived as a green technology, it is important to ensure that end-of-life issues will not be detrimental to solar energy's success. United States Environmental Protection Agency Method 1311, California waste extraction test, and modified versions of both were performed on a multi-crystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Increasing the temperature results in accelerated leaching of Cd from CdTe module pieces. The same behavior was earlier reported by Collins and Anctil [25] for the leaching of Cd from CIGS modules and Pb from c-Si modules, by increasing the leaching temperature to T = 50 • C. All of our leaching data for Cd are well described by Equation ( 2) and the C max -value for Cd, which decreases with increasing pH. This finding is in accordance with the data reported by Ramos-Ruiz [5] on leaching of Cd and Te out of CdTe modules in solutions with different pH values under simulated landfill conditions.…”
Section: Discussionsupporting
confidence: 90%
“…Increasing the temperature results in accelerated leaching of Cd from CdTe module pieces. The same behavior was earlier reported by Collins and Anctil [25] for the leaching of Cd from CIGS modules and Pb from c-Si modules, by increasing the leaching temperature to T = 50 • C. All of our leaching data for Cd are well described by Equation ( 2) and the C max -value for Cd, which decreases with increasing pH. This finding is in accordance with the data reported by Ramos-Ruiz [5] on leaching of Cd and Te out of CdTe modules in solutions with different pH values under simulated landfill conditions.…”
Section: Discussionsupporting
confidence: 90%
“…Moisture content (%) of IBAs was obtained by weight difference before and after oven drying at 105 °C for 24 h. Particle size distribution was determined with sieving of five size divisions, 0-2 mm, [2][3][4][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and total organic carbon (TOC) were measured with a TOC analyzer (multi N/C® 2100/2100S, Analytikjena). Rotor mill (ZM 200,Retsch) was used to reduce the IBA sample size below 150 µm before total element measurement.…”
Section: Iba Characterizationmentioning
confidence: 99%
“…Although pH is the most relevant factor on the assessment of the differences between leaching methods due to its strong control on the pollutant release [15], there are many other factors which may significantly affect the leaching results, such as particle size distribution, liquid to solid (L/S) ratio, leaching regents, apparatus and scale, mixing time, leaching procedures, etc. [4,[16][17][18][19][20]. So far, many of these factors have been specified among various available methods designed for leaching analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Whether the broken module is classified as hazardous or non-hazardous waste is determined by the concentration of metals during a standardised test procedure designed to simulate such leaching behaviour. There is a broad scientific discussion about the leakage behaviour of damaged PV modules in general and the suitability of standard test procedures, which is briefly summarised here [45][46][47].…”
Section: Leaching Behaviour Of Damaged Photovoltaic Modulesmentioning
confidence: 99%
“…Similarly to [51], another study [46] investigated the applicability of two US standard waste characterisation leaching tests to the leaching behaviour of PV waste (mc-Si and CIGS). The authors found that lead concentrations from mc-Si cells and modules exceeded the regulatory limit but only when measured for longer periods than specified by the standard tests.…”
Section: Leaching Behaviour Of Damaged Photovoltaic Modulesmentioning
confidence: 99%